เทคนิคการสร้างสรรค์ผลงานศิลปะให้มีเอกภาพ (Unity) อย่างร่วมมือบนความหลากหลายและยุ่งเหยิง - ศิริวิโรจน์สกุล สมศักดิ์ (Journal of Education Studies, Chulalongkorn University, 2019)
Team working is a necessary skill for a harmonious society. Artwork can help strengthen teamwork by creating “All for One – One for All” artwork using the “Jigsaw” concept (Jigsaw Art from Many Mind) is a method of producing a large piece of artwork which comprises unity, beauty and value with the unique identity of each participant being an integral part of the end result. There are five steps involved in Jigsaw Art, namely: 1) drawing the lines, 2) cutting out the shapes, 3) drawing and painting, 4) connecting the jigsaw pieces back together, and 5) showing the product of art. Using the context of “All for One – One for All” enables artists to work together in harmony, learn how to distribute work to others, take responsibility for their own pieces of the jigsaw and most importantly, everyone involved will share pride in their work of art and also take pride in the individual piece each artist produces which plays an important role in the finished product.